Dolomite catalyst for fast pyrolysis of waste cooking oil into hydrocarbon fuel - Yorinda Buyang; Reva Edra Nugraha; Holilah Holilah; Hasliza Bahruji; Suprapto Suprapto; Aishah Abdul Jalil; Muryani Muryani; Didik Prasetyoko (South African Journal of Chemical Engineering, 2023)
Dolomite as the catalyst for pyrolysis of waste cooking oil (WCO) was investigated to produce hydrocarbon fuels. Optimization of pyrolysis parameters i.e. time, temperature and catalysts loading, achieved high selectivity of WCO to diesel hydrocarbon, compared to thermal pyrolysis that produced mainly carboxylic acids. Dolomite catalysed deoxygenation of fatty acid in WCO into hydrocarbon, consequently accelerating the pyrolysis time to 75 min. Bio-oil at 68.06% yield with 57.27% selectivity towards diesel and gasoline hydrocarbons was obtained at 450 °C while using 6% of dolomite. Dolomite exhibited partial phase separation into dolomite/CaCO3 mixtures within 15 min of pyrolysis, initiated by the generated CO2 during pyrolisis of WCO. The catalyst is stable for up to three reaction cycles suggesting the activity was achieved from the synergy between the dolomite/CaCO3 phases.